Evolution of New Variants/Mutants of JE Virus, Its Effect on Neurovirulence, Antigenicity, Host Immune Responses and Disease Transmission in Endemic Areas. (3rd April 2014) - Kant Upadhyay, Ravi
Abstract : This paper highlights various reasons of evolution of new mutants/variants of JE virus and its effects on neurovirulence, antigenicity, host immune responses, and disease transmission in endemic areas. Virus is reorganizing its genome by making sequence alterations, single site mutations, cluster specific reversions, and amino acid substitutions in neutralizing antigenic sites mainly in N′ glycosylation sites and epitopic regions of S and E proteins. Virus is regularly changing gene order, gene density by making substitution point mutations in important structural genes which make virus envelope proteins. Further, JE virus acquiring new genetic variations and adaptabilities through genetic recombination of wild strains with vaccine strains and assimilating new lethal genes that lead to emergence of molecular variants/mutants. These newly emerged JE virus genotypes have attained the ability to escape the immune defense and show wider resistance against vaccines and therapeutic agents. Thus new strains did significant elevation in the level of neurovirulence, antigenicity and pathogenesis. It is causing very high mortalities in various infant groups and imposing lifelong irreversible disorders in survivors and showing a regular trend of emergence and reemergence in endemic areas. The present review article emphasizes methods to suppress virus replication, reversion of neurovirulence, attenuation and an utmost need of more potential vaccines against cross reactive heterologous genotypes of JE virus to control disease transmission and mortalities occurring in endemic areas.